G341(P) Quality improvement project to streamline acutely unwell children in a district general hospital (dgh) emergency department. (12th March 2018) - Palman, J; Miles, F; Emordi, C; Lodge, F; Stone, V; Hikmet, F; Nuti, A
Abstract : Aims: To develop a streamlined process ensuring severely unwell patients are triaged and referred directly to a specialist paediatrician within a timely fashion so that stabilisation and transfer to the ward occurs within the designated 4 hour emergency period. This quality improvement project aims to reduce the number of >4 hour patient waiting times by improving triage within the Paediatric Emergency Department (PED) and enhancing communication between the emergency and paediatric teams. This is important for DGHs with no paediatric assessment unit to monitor patients before admitting or discharging from hospital. Methods: An adapted version of the National Institute of Clinical Excellence (NICE) guidance for fever in the under 5 years (http://guidance.nice.org.uk/CG1) was created with specific thresholds to grade severity. The pathway implemented in this project, triaged high-risk patients to the paediatric team and low risk patients to the emergency team despite the method of referral. Data was prospectively collected over a 3 week period, analysed and presented in a departmental meeting and recommendations implemented for further cycles. We performed two cycles of quality improvement in this project. Results: A total of 87 and 188 patients were included in cycle 1 (C1) and cycle 2 (C2) respectively. The demographics for each cycle were similar, the average age being 1.83 and 1.48 years respectively (p=0.51). There was no statistical difference between the presenting complaints for each of the cycles (p=0.969). Average PED duration was reduced from 3:24 hours to 2:36 hours (p=0.0009). The number patients waiting >4 hours significantly reduced from C1: 17/87 (19.5%) compared to C2: 14/188 (6.9%). In C2 we investigated the outcomes of PED attendance and discharge destination. During C2, 141/188 (75%) patients were discharged, 26/188 (13.8%) patients were admitted by the paediatric team, the remaining were ambulated or referred to another specialty. Conclusion: By introducing our adapted NICE guidance pathway we demonstrated that average time spent in PED and number of children waiting >4 hours can be significantly reduced. Particularly unwell children were identified earlier and appropriately referred to the paediatricians from triage. Further cycles are underway to assess the impact of more senior cover in PED and improve the referral pathways.